2021
DOI: 10.3390/antibiotics10091129
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dalbavancin in Skin, Bone and Joint Infections: A Real-Life Experience in an Italian Center

Abstract: Dalbavancin is a lipoglycopeptide approved for the treatment of acute bacterial skin and skin structure infections (ABSSSI). The aim of the study was to evaluate the efficacy and safety in all patients who received at least one administration of dalbavancin. Methods: We carried out a retrospective study of the use of dalbavancin in 55 patients at the Azienda Ospedaliera Ospedali Riuniti Umberto I (Ancona, Italy) from February 2017 to May 2020 and compared “on label” and “off label” use of dalbavancin in ABSSSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These results are similar to those reported by Phase 3 clinical trials, which displayed clinical success in patients infected by S. aureus of 90.6% with dalbavancin and 93.8% with vancomycin/linezolid, 4 and by real-life settings. 19 , 23 , 24 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those reported by Phase 3 clinical trials, which displayed clinical success in patients infected by S. aureus of 90.6% with dalbavancin and 93.8% with vancomycin/linezolid, 4 and by real-life settings. 19 , 23 , 24 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, pharmacokinetic studies demonstrated that this new drug could reach an optimal concentration both in the bone and articular tissues [ 23 ]. Real-life dalbavancin treatment for osteomyelitis and prosthetic joint infections has been shown to be effective and safe [ 24 , 25 ]. However, to date, not many clinical data are available for spondylodiscitis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%